Estimation of Time-Averaged Shear Wave Velocity (SWV) to 30 m considering Site SWV Structural Characteristic - Zhijun Jiang; Shengcai Li; Lei Zhang; Tuo Song; Lingkun Chen (Advances in Civil Engineering)
The time-averaged shear wave velocity (SWV) to 30 m (VS30) is a site condition parameter that has been widely used to specify the site class in building codes. However, the penetration depth of some building sites is less than 30 m, and thus, VS30 cannot be determined based on the velocity profiles. To estimate the site parameter VS30 accurately, we examined the effect of the velocity structural characteristic parameter of site profiles, βH, on VS30 by performing a residual analysis. Further, a method to estimate VS30 was established considering the effect of βH, and the validity of the proposed model was assessed based on site data pertaining to Japan and California (USA). The results show that the time-averaged shear wave velocity to the depth H (H < 30 m), VSH, is weakly correlated with the parameter βH. However, βH has a significant effect on VS30; for the same site VSH, VS30 tended to increase with βH. Compared with the extrapolation method, the proposed model can significantly reduce the standard deviation for the estimation of VS30, while increasing the correlation between the estimated and measured values of VS30. Thus, the estimation accuracy can be significantly improved by considering the effect of βH.